From molecular to immuno-pharmacology: Schmiedeberg Medal for Klaus Resch - Michael U. Martin; Detlef Neumann; Michael Kracht (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Histamine H1- and H4-receptor expression in human colon-derived cell lines - Jasper Carsten Schrammel; Martin König; Miriam Frommer; Kaya Saskia Andersen; Marla Kirsten; Roland Seifert; Detlef Neumann; Bastian Schirmer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
In previous studies, we demonstrated the involvement of H 4 R in inflammatory bowel disease (IBD) and IBD-associated colon cancer in mice and could ascribe H 4 R-mediated histamine function to colon epithelial cells. The transferability of obtained data to humans is however lacking. Functional expression of H 4 R on colon epithelial cells is a prerequisite to pursue the hypothesis of involvement of H 4 R in carcinogenesis. Thus, we here compared the expression of histamine receptor subtypes in a series of cell lines. Out of these, three colon-derived cell lines displaying different combinations of H 1 R and H 4 R expression were submitted to functional analyses. Human hematopoietic HMC-1, HL-60, and U937, lung-derived A549 and Calu-3, and colorectal LoVo, SW 480, Caco-2, HT-29, and HCT116 cells were included in the study. mRNA expression was quantified by RT-qPCR. For functional analyses, Caco-2, HT-29, and HCT116 cells were treated by incubation with 1 – 10 µM histamine in the presence or absence of selective histamine receptor antagonists. Calcium mobilization, cAMP accumulation, and cell proliferation were measured by fluorimetry, mass spectrometry, and real-time bioimpedance measurements, respectively. Histamine receptor expression was heterogeneous in the cell lines tested. In most cell lines, we detected H 1 R mRNA while H 4 R mRNAs were found only occasionally. The colon-derived epithelial cell lines LoVo, SW480, and HT-29 expressed H 1 R mRNA exclusively, while in HCT116 cells H 1 R and H 4 R mRNAs and in CaCo-2 H 2 R mRNA were detectable. Subsequent functional analyses in HT29, Caco-2, and HCT116 cells, however, indicated that only HT-29 responded to histamine stimulation, by means of H 1 R. For a detailed analysis of histamine receptor function, esp. that of H 1 R and H 4 R, in human colon-derived cell lines, the cell lines tested here are not fully convenient unless genetically modified.

Probiotics in Naunyn–Schmiedeberg’s Archives of Pharmacology - Detlef Neumann; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

High constitutive Akt2 activity in U937 promonocytes: effective reduction of Akt2 phosphorylation by the histamine H2-receptor and the β2-adrenergic receptor - Kristin Werner; Detlef Neumann; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Flow cytometric analysis with a fluorescently labeled formyl peptide receptor ligand as a new method to study the pharmacological profile of the histamine H2 receptor - Kristin Werner; Solveig Kälble; Sabine Wolter; Erich H. Schneider; Armin Buschauer; Detlef Neumann; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Histamine H4-receptor expression in the brain? - Erich H. Schneider; Detlef Neumann; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Histamine induces chemotaxis and phagocytosis in murine bone marrow-derived macrophages and RAW 264.7 macrophage-like cells via histamine H4-receptor - Christoph P. Czerner; Andreas Klos; Roland Seifert; Detlef Neumann (Inflammation Research, 2014)

The dual H3/4R antagonist thioperamide does not fully mimic the effects of the ‘standard’ H4R antagonist JNJ 7777120 in experimental murine asthma - Detlef Neumann; Silke Beermann; Heike Burhenne; Silke Glage; Christina Hartwig; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Problems associated with the use of commercial and non-commercial antibodies against the histamine H4 receptor - Detlef Neumann; Silke Beermann; Lavinia Mägel; Danny Jonigk; Dorothea Weber-Steffens; Daniela Männel; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Physiologie, Pharmakologie und neue Ansätze für die Therapie der Allergie - Detlef Neumann; Roland Seifert (BIOspektrum, 2012)

Commercially available antibodies against human and murine histamine H4-receptor lack specificity - Silke Beermann; Roland Seifert; Detlef Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Systematic analysis of histamine and N-methylhistamine concentrations in organs from two common laboratory mouse strains: C57Bl/6 and Balb/c - Anna Sophie Zimmermann; Heike Burhenne; Volkhard Kaever; Roland Seifert; Detlef Neumann (Inflammation Research, 2011)

Changes of the cytoplasmic ultrastructure during development of sclerotia in Claviceps purpurea (Fr.) Tul. - Werner Lsecke; Dieter Neumann; Detlef Grger; Hans-Peter Schmauder (Archives of Microbiology, 1980)